The Metacurriculum: Guarding the Golden Apples of University Culture - DEKLE, Dawn Jeanine (Institutional Knowledge at Singapore Management University, 2004)
Presents information on the emergence of the metacurriculum from the interaction of the official curriculum and the hidden curriculum in higher education. Impact of the metacurriculum on the culture of a university; Difference between the official and the hidden curriculum; Importance of hidden curriculum on metacurriculum.